2021
DOI: 10.21608/aimj.2021.66816.1430
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine is an Excellent Additive to Local Anaesthesia for Postoperative Analgesia in Bilateral Third Molar Teeth Extraction Surgery

Abstract: Background: Extraction is still the primary treatment of choice for impact tooth under IANB or GA or a combination of both. Dexmedetomidine has been noticed to lengthen nerve blocks' range of duration, possibly due to the consequent vasoconstriction if combined with local anaesthetics. Aim of the work: This study investigates the effect of injection of Dexmedetomidine as an additive to Lidocaine in IAN for patients undergoing lower bilateral impacted tooth extraction regarding analgesia's overall quality. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…As a new imidazole derivative, dexmedetomidine has high selectivity for α2 receptor and could effectively activate α2 receptor [25]. Pharmacological studies have suggested that its biological potency is better than clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…As a new imidazole derivative, dexmedetomidine has high selectivity for α2 receptor and could effectively activate α2 receptor [25]. Pharmacological studies have suggested that its biological potency is better than clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are by a study by Singh et al [ 8 ]. The effect of DEXMED can be attributed to its local vaso-constrictive and anti-inflammatory effects; these effects may be responsible for prolonged anesthesia and good analgesia post-operatively [ 12 - 15 ]. Yamane et al [ 4 ] also found similar results when dexmedetomidine was injected locally in the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%